PERAN KOPERASI DALAM MENDUKUNG PENGUATAN UMKM KONVEKSI DI KABUPATEN PATI PADA MASA PANDEMI COVID-19 - Eva Ida Fitria Asiati; Albertus Sentot Sudarwanto (Jurnal Privat Law, 2023)
This article aims to examine the role of cooperatives in supporting the strengthening of MSMEs Convection Cloth Masks during the Covid-19 pandemic.This study uses empirical research methods. This legal research uses legal resources in the form of legal materials both primary legal materials and secondary legal materials. The data types used are Secondary data and Primary data. Data collection techniques are used through literature studies, interviews, and data analysts. The results showed that cooperatives play an active role in supporting the strengthening of MSMEs Convection in Pati Regency.